2011
DOI: 10.1111/j.1476-5381.2011.01290.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nociceptive responses after systemic administration of amidated kyotorphin

Abstract: BACKGROUND AND PURPOSEKyotorphin (KTP; L-Tyr-L-Arg), an endogenous neuropeptide, is potently analgesic when delivered directly to the central nervous system. Its weak analgesic effects after systemic administration have been explained by inability to cross the blood–brain barrier (BBB) and detract from the possible clinical use of KTP as an analgesic. In this study, we aimed to increase the lipophilicity of KTP by amidation and to evaluate the analgesic efficacy of a new KTP derivative (KTP-amide – KTP-NH2).EX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(82 citation statements)
references
References 31 publications
(39 reference statements)
1
81
0
Order By: Relevance
“…A suggested alternative mechanism for analgesia induced by KTP is their rapid degradation, resulting in free l-Arg, the substrate for nitric oxide (NO) synthase (Arima et al 1997). The NO thus formed would induce analgesia via metenkephalin release, which is the common final event leading to analgesia (Ribeiro et al 2011a). This data provides a hint for the relationship between the results obtained for KTP on ITC and intravital studies.…”
Section: Discussionmentioning
confidence: 79%
“…A suggested alternative mechanism for analgesia induced by KTP is their rapid degradation, resulting in free l-Arg, the substrate for nitric oxide (NO) synthase (Arima et al 1997). The NO thus formed would induce analgesia via metenkephalin release, which is the common final event leading to analgesia (Ribeiro et al 2011a). This data provides a hint for the relationship between the results obtained for KTP on ITC and intravital studies.…”
Section: Discussionmentioning
confidence: 79%
“…Although naloxone is an opioid antagonist, studies demonstrated KTP itself does not bind to opioid receptors, but has rather an indirect action mediated by met-enkephalin and β-endorphin, which activate δ- and/or μ-opioid receptors (Takagi et al, 1979b; Rackham et al, 1982; Ribeiro et al, 2011a). Other authors confirmed KTP-induced met-enkephalin release from guinea pig and rat brain slices (Shiomi et al, 1981; Takagi et al, 1982; Janicki and Lipkowski, 1983).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…In order to overcome these issues while preserving effectiveness as analgesic, several groups including ours have worked in different strategies to modify the original peptide. Some of these strategies deal with (i) chirality (Rybal’chenko et al, 1999; Lopes et al, 2006a), (ii) use of unnatural amino acids and substitution of peptide bonds (Dzimbova et al, 2014; Serrano et al, 2014b), (iii) conjugation with lipophilic groups (Chen et al, 1998; Wang et al, 2001; Lopes et al, 2006b; Ribeiro et al, 2011b; Serrano et al, 2014b), (iv) cationicity improvement (Ribeiro et al, 2011a). …”
Section: Development Of New Ktp Derivativesmentioning
confidence: 99%
See 2 more Smart Citations